Application of thermal microcautery in migraine management - Papageorgiou, Eleni; Kovas, Konstantine; Power, Camillus; Kostopoulos, Nikolaos (Headache Medicine, 2019)
Thermal microcautery is a novel minimally invasive intervention for migraine. We present a case series of twenty-one patients who underwent this technique. Nineteen patients reported improvement in migraine management. Of these four patients went on to complete remission and a further eleven patients reported over 50% improvement. In addition, the majority of patients noted reductions in intensity and duration of headache with a better response to medication. The efficacy of thermal microcautery generates a new hypothesis that attempts to explain how a neuromodulation technique may be helpful in the management of migraine.